49e parallèle - Powell, Michael; Young, Frederick A.; Howard, Leslie; Olivier, Laurence; Massey, Raymond (Carlotta Films, 2013)
At once a compelling piece of anti-isolationist propaganda and a quick-witted wartime thriller, 49th Parallel is a classic early work from the inimitable British filmmaking team of Michael Powell and Emeric Pressburger. When a Nazi U-boat crew, headed by the ruthless Eric Portman, is stranded in Canada during the thick of World War II, the men evade capture by hiding out in a series of rural communities, before trying to cross the border into the still-neutral United States. Both soul-stirring and delightfully entertaining, "49th Parallel" features a colorful cast of characters played by larger-than-life actors Laurence Olivier, Raymond Massey, Anton Walbrook, and Leslie Howard. [www.criterion.com]